Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env218
|View full text |Cite
|
Sign up to set email alerts
|

Activated Sludge and Biofilms: Molecular Techniques for Determining Community Composition

Abstract: Methods for Microbial Diversity Analysis in Wastewater Treatment Plants (wwtps) General Microbial Diversity in Wastewater Treatment Plants Functional Groups of Microorganisms in Treatment Plants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 130 publications
1
34
0
Order By: Relevance
“…It may have been possible to observe a larger number of the total microbiota by FISH with the use of additional probes specific for archaea and other organisms. However, as was previously observed in other studies, detection of all unknown organisms contained in the sample may be impossible by existing FISH methods due to the relatively high detection limit of approximately 10 3 -10 4 target cells per ml (Loy et al, 2002).…”
Section: Cirrhipathes Lutkenimentioning
confidence: 68%
“…It may have been possible to observe a larger number of the total microbiota by FISH with the use of additional probes specific for archaea and other organisms. However, as was previously observed in other studies, detection of all unknown organisms contained in the sample may be impossible by existing FISH methods due to the relatively high detection limit of approximately 10 3 -10 4 target cells per ml (Loy et al, 2002).…”
Section: Cirrhipathes Lutkenimentioning
confidence: 68%
“…This apparent probing anomaly could be due to problems with either ALF1b or GAM42a. ALF1b is known to be highly unspecific for Alphaproteobacteria (Loy et al 2002) and GAM42a binding inconsistencies have previously been reported (Buchholz-Cleven et al 1997, Yeates et al 2003. Full length insert sequencing of the Alphaproteobacteria and Gammaproteobacteria 16S rDNA clones obtained in our library will facilitate the design of specific probes to determine the identity and abundance of coral-associated Alphaproteobacteria or Gammaproteobacteria, and to clarify their in situ spatial arrangements and global distribution.…”
Section: Microbial Analysismentioning
confidence: 72%
“…Two clones, each representing a single-sequence OTU, were identified as chimeras and excluded from further analyses. Based on sequence similarity (97% threshold), the remaining 16S rRNA clone sequences could be grouped in the same OTUs as suggested by RFLP analysis (Table 3) (23,30). The homologous coverage curve indicated that the 56 clones covered most of the expected richness in the pooled libraries B, C, and D if a sequence similarity threshold of up to 99% is applied (Fig.…”
Section: Resultsmentioning
confidence: 91%